Pelatihan Khotib Jum’at Bagi Remaja di Desa Banjarroyo Kalibawang Kulon Progo - Yusron Masduki; Sutipyo Ru'iya (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2024)
Banjarroyo Village is one of the villages in Kalibawang District, Kulonprogo Regency, which is geographically located in a hilly area. Banjarroyo village with multicultural conditions, sociologically the people of Banjaroyo adhere to various religions. Most of the Banjarroyo people work as laborers who work in the Yogyakarta area and its surroundings, and a small number are farmers and small business actors. The people of Banjarroyo have high mobility, leaving in the morning and returning in the afternoon/evening. This kind of community condition is a challenge in itself, especially in the field of da'wah, so that mosque cadres are lacking. This service aims to grow mosque cadres, especially a Friday preacher. There is a lack of preachers in mosques in Banjarroyo, so it is very important to hold kotib training for mosque youth who will become successors in the future. The implementation method is with lectures, discussions and preaching practices. Participants came from three mosques in the Padukuhan Banjarroyo, including Slanden, Banjaran and Pantok Kulon. The implementation of this service seeks to provide insight to teenagers to always adhere to religious teachings in accordance with the word of God and the teachings of the Prophet Muhammad. Worship in accordance with the teachings of Allah and His Messenger will receive a reward from Allah SWT. The output is in the form of news in online media.